1991
DOI: 10.1007/bf00336404
|View full text |Cite
|
Sign up to set email alerts
|

Impact of long-term immunosuppression with cyclosporin A on serum lipids in stable renal transplant recipients

Abstract: To determine the impact of long-term immunosuppression on serum lipids in stable renal graft recipients we measured serum lipids and apolipoprotein B concentrations in 20 patients receiving therapy with cyclosporin (CsA) and low-dose prednisolone (CsA/P) and in 18 patients on therapy with azathioprine and maintenance steroids (Aza/P). The patients were matched for age, body mass index, primary renal disease and dose of prednisolone, but not for the duration in transplantation and serum creatinine concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 20 publications
2
15
1
Order By: Relevance
“…These findings are also corro borated by earlier studies by Hricik et al [19] in 79 adults, which showed a significant reduction of serum cholesterol after steroid withdrawal. However, our findings are in contrast to those of Schom et al [20] who showed that patients reccivingcyclosporineand prednisone have high er levels of triglycerides, total cholesterol and low-density lipoprotein levels as compared to a group of adult patients receiving azathioprine and prednisone. The limitation of that study [26] is that it did not have a population receiv ing cyclosporine alone and/or in combination with pred- eride removal [23].…”
Section: Discussioncontrasting
confidence: 56%
“…These findings are also corro borated by earlier studies by Hricik et al [19] in 79 adults, which showed a significant reduction of serum cholesterol after steroid withdrawal. However, our findings are in contrast to those of Schom et al [20] who showed that patients reccivingcyclosporineand prednisone have high er levels of triglycerides, total cholesterol and low-density lipoprotein levels as compared to a group of adult patients receiving azathioprine and prednisone. The limitation of that study [26] is that it did not have a population receiv ing cyclosporine alone and/or in combination with pred- eride removal [23].…”
Section: Discussioncontrasting
confidence: 56%
“…Immunosuppressive therapy has been reported to increase, decrease or leave HDL levels unaffected [5,10,11,24]. Parallel changes in plasma apoA-I levels are usually observed.…”
Section: Plasma Hdlmentioning
confidence: 91%
“…Plasma LDL levels appear to be consistently elevated by CsA [4,5,6,7,9,10,13,14] even in patients where plasma VLDL levels are not altered [5,6,9,13]. A correlation between CsA levels and plasma LDL-C has been described in some studies [19], but was not observed in others [5,20].…”
Section: Plasma Ldlmentioning
confidence: 91%
See 2 more Smart Citations